Modified TMAH based etchant for improved etching characteristics on Si1 0 0 wafer. (27th June 2017) - Swarnalatha, V; Narasimha Rao, A V; Ashok, A; Singh, S S; Pal, P
Abstract: Wet bulk micromachining is a popular technique for the fabrication of microstructures in research labs as well as in industry. However, increasing the throughput still remains an active area of research, and can be done by increasing the etching rate. Moreover, the release time of a freestanding structure can be reduced if the undercutting rate at convex corners can be improved. In this paper, we investigate a non-conventional etchant in the form of NH2 OH added in 5 wt% tetramethylammonium hydroxide (TMAH) to determine its etching characteristics. Our analysis is focused on a Si1 0 0 wafer as this is the most widely used in the fabrication of planer devices (e.g. complementary metal oxide semiconductors) and microelectromechanical systems (e.g. inertial sensors). We perform a systematic and parametric analysis with concentrations of NH2 OH varying from 5% to 20% in step of 5%, all in 5 wt% TMAH, to obtain the optimum concentration for achieving improved etching characteristics including higher etch rate, undercutting at convex corners, and smooth etched surface morphology. Average surface roughness ( R a ), etch depth, and undercutting length are measured using a 3D scanning laser microscope. Surface morphology of the etched Si1 0 0 surface is examined using a scanning electron microscope. Our investigation has revealed a two-fold increment in the etch rate of a 1 0 0 surface with the addition of NH2 OH in the TMAH solution. Additionally, the incorporation of NH2 OH significantly improves the etched surface morphology and the undercutting at convex corners, which is highly desirable for the quick release of microstructures from the substrate. The results presented in this paper are extremely useful for engineering applications and will open a new direction of research for scientists in both academic and industrial laboratories.